SpaceOps 2014 Conference 2014
DOI: 10.2514/6.2014-1606
|View full text |Cite
|
Sign up to set email alerts
|

Launch Vehicle Production and Operations Cost Metrics

Abstract: Traditionally, launch vehicle cost has been evaluated based on $/Kg to orbit. This metric is calculated based on assumptions not typically met by a specific mission. These assumptions include the specified orbit whether Low Earth Orbit (LEO), Geostationary Earth Orbit (GEO), or both. The metric also assumes the payload utilizes the full lift mass of the launch vehicle, which is rarely true even with secondary payloads. 1,2,3Other approaches for cost metrics have been evaluated including unit cost of the launch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…The next disadvantage is that, particularly, in the space industry the traditional plan‐driven approach are typically long lead times on hardware development . A study done by Watson, Neeley, and Blackburn at NASA found that 2 of the major drivers of launch vehicle cost was production of development hardware and development test cost. Based on NASA's study, one can easily understand how dragging out one of the more costly phases of development could prove challenging.…”
Section: Plan‐driven Life‐cycle Approachmentioning
confidence: 99%
“…The next disadvantage is that, particularly, in the space industry the traditional plan‐driven approach are typically long lead times on hardware development . A study done by Watson, Neeley, and Blackburn at NASA found that 2 of the major drivers of launch vehicle cost was production of development hardware and development test cost. Based on NASA's study, one can easily understand how dragging out one of the more costly phases of development could prove challenging.…”
Section: Plan‐driven Life‐cycle Approachmentioning
confidence: 99%